Flow through a porous medium and ground heat exchangers - Iosif-Stylianou, Iosifina; Christodoulides, Paul; Aresti, Lazaros; Tassou, Savvas A.; Florides, Georgios A. (My University, 2021)
The thermal response of vertical Ground Heat Exchangers (GHEs) is examined when the ground sublayer involves underground water flow. A numerical model constructed to allow for the presence of porous media regions and a consequent validated computational finite elements model in FlexPDE software lead to an analysis of several factors effecting the efficiency of the GHE, such as summer and winter mode of operation, underground temperature variation in small depths, borehole radius, borehole grout properties, U-tube diameter, U-tube leg and borehole centers distance, groundwater flow velocity.